Adopted orphans as regulators of inflammation, immunity and skeletal homeostasis - Ipseiz, Natacha; Scholtysek, Carina; Culemann, Stephan; Krönke, Gerhard (Swiss Medical Weekly, 2014)
Adopted orphan nuclear receptors, such as peroxisome proliferator-activated receptors (PPARs) and liver X receptors (LXRs), have emerged as key regulators of inflammation and immunity and likewise control skeletal homeostasis. These properties render them attractive targets for the therapy of various inflammatory and autoimmune diseases affecting the musculoskeletal system. This review summarises the current knowledge on the role of these families of receptors during innate and adaptive immunity as well as during the control of bone turnover and discuss the potential use of targeting these molecules during the treatment of chronic diseases such as osteoarthritis, rheumatoid arthritis and osteoporosis.
EVALuna2:13065

Corrigendum to "Fc-gamma receptors are not involved in cartilage damage during experimental osteoarthritis" [Osteoarthritis Cartilage 23 (2015) 1221-1225] - Stock, Michael; Distler, A.; Distler, Jörg; Beyer, Christian; Ruiz-Heiland, G.; Ipseiz, Natacha; Seeling, Michaela; Krönke, Gerhard; Nimmerjahn, Falk; Schett, Georg (Osteoarthritis and Cartilage, 2016)
EVALuna2:13371

Microbiota from Obese Mice Regulate Hematopoietic Stem Cell Differentiation by Altering the Bone Niche - Luo, Yubin; Chen, Guangliang; Hannemann, Nicole; Ipseiz, Natacha; Krönke, Gerhard; Bäuerle, Tobias; Munos, Luis; Wirtz, Stefan; Schett, Georg; Bozec, Aline (Cell Metabolism, 2015)
The effect of metabolic stress on the bone marrow microenvironment is poorly defined. We show that high-fat diet (HFD) decreased long-term Lin(-)Sca-1(+)c-Kit(+) (LSK) stem cells and shifted lymphoid to myeloid cell differentiation. Bone marrow niche function was impaired after HFD as shown by poor reconstitution of hematopoietic stem cells. HFD led to robust activation of PPAR?2, which impaired osteoblastogenesis while enhancing bone marrow adipogenesis. At the same time, expression of genes such as Jag-1, SDF-1, and IL-7 forming the bone marrow niche was highly suppressed after HFD. Moreover, structural changes of microbiota were associated to HFD-induced bone marrow changes. Antibiotic treatment partially rescued HFD-mediated effects on the bone marrow niche, while transplantation of stools from HFD mice could transfer the effect to normal mice. These findings show that metabolic stress affects the bone marrow niche by alterations of gut microbiota and osteoblast-adipocyte homeostasis.
EVALuna2:1968

Regulation of autoantibody activity by the IL-23-TH17 axis determines the onset of autoimmune disease. - Pfeifle, René; Rothe, Tobias; Ipseiz, Natacha; Scherer, Hans U.; Culemann, Stephan; Harre, Ulrike; Ackermann, Jochen; Seefried, Martina; Kleyer, Arnd; Uderhardt, Stefan; Haugg, Benjamin; Huebert, Axel J.; et al. (Nature Immunology, 2017)
The checkpoints and mechanisms that contribute to autoantibody-driven disease are as yet incompletely understood. Here we identified the axis of interleukin 23 (IL-23) and the TH17 subset of helper T cells as a decisive factor that controlled the intrinsic inflammatory activity of autoantibodies and triggered the clinical onset of autoimmune arthritis. By instructing B cells in an IL-22- and IL-21-dependent manner, TH17 cells regulated the expression of β-galactoside α2,6-sialyltransferase 1 in newly differentiating antibody-producing cells and determined the glycosylation profile and activity of immunoglobulin G (IgG) produced by the plasma cells that subsequently emerged. Asymptomatic humans with rheumatoid arthritis (RA)-specific autoantibodies showed identical changes in the activity and glycosylation of autoreactive IgG antibodies before shifting to the inflammatory phase of RA; thus, our results identify an IL-23-TH17 cell-dependent pathway that controls autoantibody activity and unmasks a preexisting breach in immunotoleranc

The nuclear receptor Nr4a1 mediates anti-inflammatory effects of apoptotic cells - Ipseiz, Natacha; Uderhardt, Stefan; Scholtysek, Carina; Steffen, Martin; Schabbauer, Gernot; Bozec, Aline; Schett, Georg; Krönke, Gerhard (Journal of Immunology, 2014)
Uptake of apoptotic cells (ACs) by macrophages ensures the nonimmunogenic clearance of dying cells, as well as the maintenance of self-tolerance to AC-derived autoantigens. Upon ingestion, ACs exert an inhibitory influence on the inflammatory signaling within the phagocyte. However, the molecular signals that mediate these immune-modulatory properties of ACs are incompletely understood. In this article, we show that the phagocytosis of apoptotic thymocytes was enhanced in tissue-resident macrophages where this process resulted in the inhibition of NF-?B signaling and repression of inflammatory cytokines, such as IL-12. In parallel, ACs induced a robust expression of a panel of immediate early genes, which included the Nr4a subfamily of nuclear receptors. Notably, deletion of Nr4a1 interfered with the anti-inflammatory effects of ACs in macrophages and restored both NF-?B signaling and IL-12 expression. Accordingly, Nr4a1 mediated the anti-inflammatory properties of ACs in vivo and was required for maintenance of self-tolerance in the murine model of pristane-induced lupus. Thus, our data point toward a key role for Nr4a1 as regulator of the immune response to ACs and of the maintenance of tolerance to "dying self."
EVALuna2:12878